“Moyers roulette”, auxiliary instrument for the mixed dentition analysis based in the lineal regression ecuation by minimal squares. - Marengo Castillo, Héctor (2020)
Objective. This study aimed to project the data from Moyers tables through linear regression equations and present a new instrument that facilitates the analysis of Moyers in mixed dentition. methods. The classical tables of Moyers were used through four linear equations projected data for both values, men and women, the roulette was built from a new table with values projected from the 19 mm to 30,5 mm corresponding to the sum of the lower incisors. Linear regression and linear equations were used to project values for both, maxilla and mandible. Roulette model was devised following the Korkhaus Orthometer model and emulating the classic medical gestation tables. Results. Two tables were obtained with new data values from 19 mm to 30,5 mm measurement, measures which correspond to the sum of the mesiodistal width of the lower incisors. The new values include projections for both, the maxilla and the mandible. Conclusion. The “roulette” is an instrument that permits find Moyers values for arch discrepancy measure in mixed dentition whith more precision and facility.